THE INFLUENCE OF PROFITABILITY, DER, AND EPS ON SHARE PRICES OF PUBLIC COMPANIES IN THE HEALTHCARE SECTOR - Kurniawan, Raden; Aghe Africa, Laely (IQTISHADequity jurnal MANAJEMEN, 2024)
ABSTRACT This research aims to determine the effect of profitability, DER (Debt to Equity Ratio) and EPS (Earning Per Share) on share prices. This research uses 49 healthcare sector financial report data for a period of 5 years, namely between 2016 and 2020. In this research, several independent variables are used, including Profitability which is proxied by the ROA (Return On Asset) ratio, DER (Debt to Equity Ratio) and EPS (Earnings Per Share). The results of this research are that ROA and EPS have an effect on share prices and DER has no effect on share prices ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh profitabilitas, DER (Debt to Equity Ratio) dan EPS (Earning Per Share) terhadap Harga Saham. Penelitian ini menggunakan sebanyak 49 data laporan keuangan sector healthcare dengan periode selama kurun waktu 5 tahun yaitu antara tahun 2016 sampai dengan tahun 2020. dalam penelitian ini menggunakan beberapa variabel indepeneden antara lain Profitabilitas yang diproksikan dengan rasio ROA (Return On Asset), DER (Debt to Equity Ratio) dan EPS (Earning Per Share). Adapun hasil dari penelitian ini adalah bahwa bahwa ROA dan EPS berpengaruh terhadap Harga Saham dan DER tidak berpengaruh terhadap Harga Saham.